Accounting research groups and their characteristics according to the model of the Ministry of Science and Technology as 2019 in Colombia - Patiño-Jacinto, Ruth Alejandra; Lezama Palomino, Juan Carlos; Burgos Rolón, Samuel David; Valero Zapata, Gloria Milena; Macías-Cardona, Hugo A. (Cuadernos de Administración, 2021)
This work aims to identify the current state of Colombian accounting research groups and consider the changes compared to previous studies. For this, a systematic analysis of the official information registered by the groups on the platforms of the Ministry of Science and Technology (Minciencias) was carried out. In the results, the accounting groups are differentiated from those with a single accounting component, including different disciplines. Active researchers, research lines, publications, and the concentration of activities within the national geography are analysed. The methodology used is qualitative, based on the documentary review of the Minciencias databases: GrupLac for groups and CvLac for the information of researchers. The main result is that the accounting research groups have increased significantly and have generated a relevant production for the Colombian context. The study’s main limitation is that only the information registered in Minciencias was analysed, omitting other possible sources that do not have the information well systematized.